SNACK BAR REDMUNG TEPUNG KACANG MERAH DAN TEPUNG KACANG HIJAU SEBAGAI MAKANAN SELINGAN SUMBER ISOFLAVON DAN SERAT - Dea Intania Gustiani; Roro Nur Fauziyah; Dadang Rosmana; Nia Fatimah Nurjanah (Poltekkes Kemenkes Bandung, 2020)
Redmung Snack Bar is made by from red bean flour and mung bean flour. Red bean flour and mung bean flour are food sources of isoflavone and fiber. The purpose of this research is to get a balance snack bar that is suitable for the receiving power, levels of isoflavones, and fiber levels required. The design of this research is experimental with complete random draft (RAL). The research methods use hedonic tests for the favorite levels, literary tests for isoflavone levels, and enzymatic gravimetric for fiber content. The research involved 30 somewhat trained panelist who is a student of nutrition department in Poltekkes Bandung. Data was analysed using the Kruskal Wallis’s test and continued with Mann Whitney's test. The results of hedonic test studies show that Formula 1 with a balance of 90% red bean flour: 10% of mung bean flour has the highest level of taste in colour and fragrance while on aspects of flavor and texture, Formula 3 with balance 50% flour Red beans: 50% of mung bean flour has the highest level of delight. Mann Whitney test Results show Formula 1 has a meaningful difference between the three formulas so that Formula 1 is set as the selected formula. In 1 food dose Snack Bar Redmung (35 g) contains isoflavone of 3.1 mg and is able to adequately 25%-42% the need for Isoflavone, and contains a fiber of 5.495 G and able to adequately 88.63% fiber needs.